Acclimation of the Marine Diatom Pseudo‐nitzschia australis to Different Salinity Conditions: Effects on Growth, Photosynthetic Activity, and Domoic Acid Content1. Issue 1 (15th November 2019) - Ayache, Nour; Hervé, Fabienne; Lundholm, Nina; Amzil, Zouher; Caruana, Amandine M. N.
Abstract : Toxic Pseudo‐nitzschia australis strains isolated from French coastal waters were studied to investigate their capacity to adapt to different salinities. Their acclimation to different salinity conditions (10, 20, 30, 35, and 40) was studied on growth, photosynthetic capacity, cell biovolume, and domoic acid (DA) content. The strains showed an ability to acclimate to a salinity range from 20 to 40, with optimal growth rates between salinities 30 and 40. The highest cell biovolume was observed at the lowest salinity 20 and was associated with the lowest growth rate. Salinity did not affect the photosynthetic activity; F v / F m values and the pigment contents remained high with no significant difference among salinities. An enhanced production of zeaxanthin was, however, observed in the late stationary and decline phases in all cultures except for those acclimated to salinity 20. In terms of cellular toxin content, DA concentrations were 2 to 3‐fold higher at the lowest salinity (20) than at the other salinities and were combined with a low amount of dissolved DA. The fact that P. australis accumulate more DA per cell in less saline waters, illustrates that climate‐related changes in salinity may affect Pseudo‐nitzschia physiology through direct effects on growth, physiology, and toxin content.